LITERATURE REVIEW APPLE Inc. STRATEGY IN DOMINATION OF THE TECHNOLOGY PRODUCT MARKET IN INDONESIA FROM 2015-2019 - Akhmad Auliya Fatahilah; Putri Giovaningrum; Hadi Supratikta (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
Technology company Apple Inc. is a market leader in IOS-based Smartphone sales. In market control, this company can quickly expand its sales wings with its official distributors to be able to reach several countries, especially buyers. The resulting products have a fairly good strategic power targeting the middle to upper segments. The methodology is exposed that the marketing of the products used leads to premium services and digital media-based distribution. The strategy adopted by Apple Inc. has proven to be very effective because the introduction of products that have an exclusive image makes loyal customers wait for the presence of their products until they reach their official distributors. By conducting good research and development (R&D) on its product line, it makes it challenging to run the market to the global corner. This study provides strategy and understanding of the business perspective of Apple Inc. technology.